(untitled) (Bangladesh Medical Journal, 2020)
First 28 days are the most vulnerable period for every neonate. Children usually suffered from respiratory illness. Therefore it is important to observe the prevalence of neonatal respiratory sickness. However, the disease profile among the neonates in rural areas is not exactly known. Many fathers in the rural area used smoke-producing tobacco. Therefore it is important to identify any relation of passive smoking with neonatal respiratory morbidities at the grass-root level.This study was conducted to estimate the frequency and to determine the pattern of respiratory illness of neonate and also to assess the impact of fathers smoking on the magnitude of acute respiratory tract infections (ARI) of newborns. This was a descriptive type of cross sectional study. It carried out on 62 neonates for 180 days, who attended the Tungipara UHC, Gopalganj in Bangladesh between January to June 2018. Data were collected through face-to-face interviews, physical examination, relevant investigations, and data were collected by semi structured questionnaire for respiratory illness. In this observational study, out of 62 neonates, from 1st day to 28 days of age. Diseases of the respiratory system topped the list (32%). Upper respiratory tract illnesses (URTI) were 22.5% as against only 9.5% of lower respiratory tract illness (LRTI). Most (47%) newborns were 28 days aged and 2nd most common (17.5%) was 15 days. The cumulative frequency was 37 percent up to 15 days of age. In the case of the father’s occupation, most (19%) were in the private service. About one third (29%) fathers were engaged in business, whereas 18% done small business among them. However, it is a village area their cultivator was only 05 fathers. Consequently parent’s education more than half (51.5%, 59.5%) were up to class 8. Nearly one-fifth of the fathers studied more than 12 classes. One-tenth of the fathers had no history of schooling and it was 1.5% of mothers. Most (32%) came in the OPD due to RTI and other than the respiratory problem was 26%. Among them, 42% did not require any treatment. In the inferential statistics fathers, smoking was responsible for neonatal respiratory illness. (Fisher’s exact test 21.87 df 4 P 001). The respiratory illness affected more by second hand smoking whose fathers smoked tobacco. There need more grass-root level, multicentric, control-based study to find out the real picture of neonate respiratory morbidity, and other illness. Bangladesh Med J. 2020 May; 49(2) : 30-33